Accidental displacement of third molar root into the lingual pouch: A case report and review of treatment approaches - Mudit Agarwal; R Muthunagai; Amit Agarwal; Himanshu Aeran (Wolters Kluwer Medknow Publications, 2021)
Third molar surgery is the most common procedure performed by oral and maxillofacial surgeons. A thorough understanding of the complications associated with this procedure will enable the practitioner to identify and counsel high-risk patients, appropriately manage more common complications, and be cognizant of less common sequelae and the most effective methods of management. We present a case of displaced third molar root into the lingual pouch (submandibular space) and ways to prevent and manage this rare complication. In this article, we have compared different surgical approaches for the removal of displaced root from the submandibular space.